2009
DOI: 10.1103/physreve.80.036404
|View full text |Cite
|
Sign up to set email alerts
|

Ponderomotive acceleration of hot electrons in tenuous plasmas

Abstract: The oscillation-center Hamiltonian is derived for a relativistic electron injected with an arbitrary momentum in a linearly polarized laser pulse propagating in tenuous plasma, assuming that the pulse length is smaller than the plasma wavelength. For hot electrons generated at collisions with ions under intense laser drive, multiple regimes of ponderomotive acceleration are identified and the laser dispersion is shown to affect the process at plasma densities down to 10 17 cm −3 . Assuming a/γg 1, which preven… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…which is now superponderomotive by a factor of four. In the papers by Geyko et al [22,23], the snowplow theory is derived by a different approach, however when it is re-cast in the terms used in this paper we have found that equation ( 8) in [23] is identical to equation (7) for Π = 1. We have also found that, from equation (5) in [23] one can obtain equation (6).…”
Section: Theorymentioning
confidence: 66%
See 1 more Smart Citation
“…which is now superponderomotive by a factor of four. In the papers by Geyko et al [22,23], the snowplow theory is derived by a different approach, however when it is re-cast in the terms used in this paper we have found that equation ( 8) in [23] is identical to equation (7) for Π = 1. We have also found that, from equation (5) in [23] one can obtain equation (6).…”
Section: Theorymentioning
confidence: 66%
“…Independently of Sazegari, Mendonca et al proposed nearly the same concept around the same time [21]. The idea has also appeared in the work of Geyko and coworkers [22,23]. Discussion of this, and similar ideas, can be found in [24].…”
Section: Introductionmentioning
confidence: 81%
“…More interesting phenomena happen when the laser field becomes strong. For example, when a ≈ 1 is relativistically strong but the resulting E x ≈ 0.3E c is below the Schwinger field, the simulation recovers what happens in classical plasmas (McKinstrie and Startsev, 1996;Naumova et al, 2004;Geyko et al, 2009). First, let us look at what happens to charged particles.…”
Section: From Laser Wakefield Acceleration To Schwinger Pair Productionmentioning
confidence: 71%
“…[12] It is noted that δ can significantly affect the dynamics of hot electrons. [13] For simplicity we ignore it because we just discuss problem in this paper for the cold electron and circular polarized laser pulses, thus, the Hamiltonian is reduced to…”
Section: Basic Formulationsmentioning
confidence: 99%